ANTIMICROBIAL ACTIVITY OF DRACAENA CINNABARI RESIN FROM SOQOTRA ISLAND ON MULTI DRUG RESISTANT HUMAN PATHOGENS - Ansari, Mohammad Javed; Al-Ghamdi, Ahmad; Al-Waili, Noori; Adgaba, Nuru; Khan, Khalid Ali; Amro, Abdulraouf (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: Few studies showed that Dracaena cinnabari resin, collected from Soqotra Island, Yemen, has antimicrobial activity. This study is the first to investigate antimicrobial activity of the resin on both antibiotic multi-resistant human pathogens and on poly-microbial culture. Material and Methods: Antimicrobial activity of ethanolic extract of Dracaena cinnabari resin from Soqotra Island on multidrug resistant Gram-positive and Gram-negative human ATCC standard pathogens and Ascosphaera apis, the causal organism of chalkbrood disease of honeybee was studied using the agar disc diffusion method. The minimal inhibitory concentration of extracts was carried out by the broth micro dilution method. Results: Ethanolic extract of Dracaena cinnabari resin showed a considerable antimicrobial activity against all the pathogens tested. The zone of inhibition were between 4.9-11.5 mm. The most sensitive microbe was Staphylococcus aureus and least sensitive was Aspergillus nidulans. The minimal inhibitory concentration of the extract against Escherichia. coli ATCC 10402, Klebsiella pneumonia ATCC 10031, and Staphylococcus aureus ATCC 29212 was 1.25 μg/mL (w/v) and for the other pathogens (Candida albicans ATCC 10231, Salmonella typhimurum ATCC 3311 and Pseudomonos aeruginosa ATCC 2785) was 2.5 μg/mL (w/v). Conclusion: Ethanolic extract of Dracaena cinnabari resin has a considerable antimicrobial activity against Gram-positive and Gram-negative human pathogens and fungi. This extract might possess a role in the management of microbial infections in human and honeybee disease.